Initial intracellular proteome profile of Aspergillus niger biofilms - Villena, Gretty K. (2009)
An initial profiling of the intracellular proteome of Aspergillus niger ATCC 10864 biofilm cultures developed on polyester cloth was carried out by using 2D-PAGE and MS-TOF analysis and it was compared to the proteome of conventionally grown free-living submerged cultures. A number of 2D-PAGE protein spots from both types of cultures were subjected to MS-TOF analysis and data interrogation of the NCBI nr database available for this species. Proteomic maps showed different expression patterns in both culture systems with differentially expressed proteins in each case. In biofilm cultures, 19% and 32% of the selected protein spots were over- expressed and differentially expressed, respectively. On the contrary, in free-living cultures, 44% and 7% of the selected protein spots were over-expressed and differentially expressed, respectively. Although preliminary, results presented in this paper show that there are significant differences between the proteomes of A. niger biofilm and free-living mycelia. It seems that cell adhesion is the most important stimulus responsible for biofilm development which is the basis of Surface Adhesion Fermentation.